(untitled) (Journal of the College of Basic Education, 2022)
The research aims to:1- Monitoring electronic information services located in the central library of the University of Technology.2- Knowing the use of web applications to provide electronic information services in the central library of the University of Technology.The research relied on the survey method, the research community consisted of 2635 beneficiaries, and the deliberate stratified proportional sample was chosen to represent the study community, where the members of the research community who had library identities were counted (2320), and 5% was taken to represent the size of the community and the research sample numbered 116 beneficiaries, and the research reached A number of results are:1- Most of the beneficiaries prefer to visit the site to obtain services before going to the library.2- The presence of a page on the social networking site, such as Facebook, Twitter and Google, as it appeared through responses